Prävention der akuten Nierenschädigung beim kritisch kranken Patienten - Joannidis, Michael; Klein, S. J.; John, S.; Schmitz, M.; Czock, David; Druml, W.; Jörres, A.; Kindgen-Milles, D.; Kielstein, J. T.; Oppert, M.; Schwenger, V.; Willam, C.; et al. (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2018)
BackgroundAcute kidney injury (AKI) has both high mortality and morbidity.ObjectivesTo prevent the occurrence of AKI, current recommendations from the renal section of the DGIIN (Deutschen Gesellschaft für Internistische Intensivmedizin und Notfallmedizin), ÖGIAIN (Österreichischen Gesellschaft für Internistische und Allgemeine Intensivmedizin und Notfallmedizin) and DIVI (Deutschen Interdisziplinären Vereinigung für Intensiv- und Notfallmedizin) are stated.Materials and methodsThe recommendations stated in this paper are based on the current Kidney Disease Improving Global Outcomes (KDIGO) guidelines, the published statements of the “Working Group on Prevention, AKI section of the European Society of Intensive Care Medicine” and the expert knowledge and clinical experience of the authors.ResultsCurrently there are no approved clinically effective drugs for the prevention of AKI. Therefore the mainstay of prevention is the optimization of renal perfusion by improving the mean arterial pressure (>65 mm Hg, higher target may be considered in hypertensive patients). This can be done by vasopressors, preferably norepinephrine and achieving or maintaining euvolemia. Hyperhydration that can lead to AKI itself should be avoided. In patients with maintained diuresis this can be done by diuretics that are per se no preventive drug for AKI. Radiocontrast enhanced imaging should not be withheld from patients at risk for AKI; if indicated, however, the contrast media should be limited to the smallest possible volume.
Gesehen am 12.11.2019